Quest of the three Worlds : - Smith, Cordwainer (Ace Books, Inc, 1966)
Contents: It is the era of the rediscovery of man and Casher O'Neill holds in his hand the conscience of the planet Mizzer. Armed with an all-world travel pass, initially his quest is for freedom - to rid the Twelve Niles of the dictator who has usurped his rightful place - but it changes as time goes on